Complex neonatal neurological anomalies: A case report of hydrocephalus, hydranencephaly, and holoprosencephaly - Muhammad Ilham; Febriani Febriani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Hydrocephalus, hydranencephaly, and holoprosencephaly are severe neurodevelopmental disorders that significantly impact brain structure and function. Early identification and appropriate management are essential to reduce morbidity and mortality, yet clinical differentiation among these conditions remains challenging. Purpose: To explore the pathophysiological mechanisms, clinical outcomes, and current management approaches for hydrocephalus, hydranencephaly, and holoprosencephaly, with a focus on improving diagnostic accuracy and therapeutic strategies. Method: This retrospective study was conducted at Arifin Achmad Hospital, Pekanbaru, over a five-year period (July 2018–July 2023), reviewing medical records of neonates diagnosed with major neurological anomalies such as hydrocephalus, hydranencephaly, and holoprosencephaly, confirmed by imaging or clinical evaluation. Results: The findings reveal that hydrocephalus is primarily characterized by abnormal cerebrospinal fluid accumulation, hydranencephaly involves near-complete cerebral hemisphere loss replaced by cerebrospinal fluid, and holoprosencephaly results from impaired prosencephalon division during early embryogenesis. Advances in genetic testing and neuroimaging have enhanced differential diagnosis, while early neurosurgical intervention and multidisciplinary care significantly improve survival and quality of life. Conclusion: Understanding the distinct pathophysiology and outcomes of these disorders is crucial for effective patient care. Future research in genetic and neurodevelopmental pathways offers promising opportunities for targeted therapies and improved long-term management.